Bstan po Lha-sras Dar-ma daʼn deʼi rjes su byuṅ baʼi rgyal rabs mdor bsdus - Karmay, Samten Gyaltsen. (Bod kyi dpe mdzod khaṅ, 1986)
History of Tibet from 9th to 11th cent., with special reference to the reign of Glaṅ-dar-ma, 803-842, the 41st king of Tibet.
In Tibetan.
Includes bibliographical references (p. 55-56).
History of Tibet from 9th to 11th cent., with special reference to the reign of Glaṅ-dar-ma, 803-842, the 41st king of Tibet.
2
Keywords: Tibet Autonomous Region (China) / History